Inclusion complexes of 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin with 2-hydroxypropyl-(-cyclodextrin: solubility and antimicrobial activity - Jasmina Hadžiabdić; Selma Špirtović-Halilović; Amar Osmanović; Lejla Zahirović; Amar Elezović (Universidade de São Paulo, 2022)
Abstract The aim of the present study is to improve the solubility and antimicrobial activity of 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin by formulating its inclusion complexes with 2-hydroxypropyl-β-cyclodextrin in solution and in solid state. The phase solubility study was used to investigate the interactions between 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin and 2-hydroxypropyl-β-cyclodextrin and to estimate the molar ratio between them. The structural characterization of binary systems (prepared by physical mixing, kneading and solvent evaporation methods) was analysed using the FTIR-ATM spectroscopy. The antimicrobial activity of 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin and inclusion complexes prepared by solvent evaporation method was tested by the diffusion and dilution methods on various strains of microorganisms. The results of phase solubility studies showed that 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin formed the inclusion complexes with 2-hydroxypropyl-β-cyclodextrin of AP type. The solubility of 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin was increased 64.05-fold with 50% w/w of 2-hydroxypropyl-β-cyclodextrin at 37 oC. The inclusion complexes in solid state, prepared by the solvent evaporation method, showed higher solubility in purified water and in phosphate buffer solutions in comparison with 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin alone. The inclusion complexes prepared by solvent evaporation method showed higher activity on Bacillus subtilis and Staphylococcus aureus compared to uncomplexed 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin due to improved aqueous solubility, thus increasing the amount of available 3-(3-(2-chlorophenyl)prop-2-enoyl)-4-hydroxycoumarin that crosses the bacterial membrane.